In vivo imaging of cellular proliferation in colorectal cancer using positron emission tomography. Issue 11 (21st October 2003) - Francis, D L; Freeman, A; Visvikis, D; Costa, D C; Luthra, S K; Novelli, M; Taylor, I; Ell, P J
Abstract : Background and aims: Positron emission tomography (PET) using 18 F labelled 2-fluoro-2-deoxy-D-glucose ( 18 FDG) is an established imaging tool, although the recent development of a biologically stable thymidine analogue [18F] 3′-deoxy-3-fluorothymidine ( 18 FLT) has allowed PET to image cellular proliferation by utilising the salvage pathway of DNA synthesis. In this study, we have compared uptake of 18 FLT and 18 FDG with MIB-1 immunohistochemistry to evaluate the role of PET in quantifying in vivo cellular proliferation in colorectal cancer (CRC). Patients and methods: Patients with resectable, primary, or recurrent CRC were prospectively studied. Thirteen lesions from 10 patients (five males, five females), median age 68 years (range 54–87), were evaluated. Patients underwent 18 FDG and 18 FLT PET scanning. Tracer uptake within lesions was quantified using standardised uptake values (SUVs). Histopathological examination and MIB-1 immunohistochemistry were performed on all lesions, and proliferation quantified by calculating a labelling index (% of MIB-1 positively stained nuclei within 1500 tumour cells). Results: Histology confirmed adenocarcinoma in 12 of 13 lesions; the remaining lesion was reactive. All eight extrahepatic lesions were visualised using both 18 FLT and 18 FDG. Three of the five resected liver metastases were also avid for 18 FLT and showed high proliferation, while the remaining two lesions which demonstrated no uptake of 18 FLT had correspondingly very low proliferation. There was a statistically significant positive correlation ( r =0.8, p<0.01) between SUVs of the tumours visualised with 18 FLT and the corresponding MIB-1 labelling indices. No such correlation was demonstrated with 18 FDG avid lesions ( r =0.4). Conclusions: 18 FLT PET correlates with cellular proliferation markers in both primary and metastatic CRC. This technique could provide a mechanism for in vivo grading of malignancy and early prediction of response to adjuvant chemotherapy.